2001
DOI: 10.1007/bf02703638
|View full text |Cite
|
Sign up to set email alerts
|

Why genetic information processing could have a quantum basis

Abstract: Living organisms are not just random collections of organic molecules. There is continuous information processing going on in the apparent bouncing around of molecules of life. Optimisation criteria in this information processing can be searched for using the laws of physics. Quantum dynamics can explain why living organisms have 4 nucleotide bases and 20 amino acids, as optimal solutions of the molecular assembly process. Experiments should be able to tell whether evolution indeed took advantage of quantum dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…It is possible that, for example, the rate of transport of large molecules is determined by the same inequality. Patel (2001) suggested that the genetic code is a consequence of the quantum search algorithm. Based on Grover's algorithm, Patel concluded that the effectiveness of the quantum search (equal to √ N = 2) will be two-fold higher than that of the classical search.…”
Section: Entangled Quantum States Of Biologically Important Moleculesmentioning
confidence: 99%
“…It is possible that, for example, the rate of transport of large molecules is determined by the same inequality. Patel (2001) suggested that the genetic code is a consequence of the quantum search algorithm. Based on Grover's algorithm, Patel concluded that the effectiveness of the quantum search (equal to √ N = 2) will be two-fold higher than that of the classical search.…”
Section: Entangled Quantum States Of Biologically Important Moleculesmentioning
confidence: 99%
“…Its predictions match the number of building blocks involved in genetic languages (i.e. N = 4, 10, 20 for Q = 1, 2, 3 respectively (Patel, 2001)), when a query is identified with nucleotide base-pairing; no other purposeful explanation of these numbers is known. Explicitly, DNA/RNA have an alphabet of 4 nucleotide bases identified with 1 base pairing, polypeptides have an alphabet of 20 amino acids identified by 3 base pairings, and a single class of 10 amino acids can be identified by 2 base pairings.…”
Section: Gug Valmentioning
confidence: 70%
“…Information may be processed by associating it with qubits; importantly, the processing efficiency is enhanced because quantum superposition and entanglement represent a type of computational parallelism [18]. Several researchers have spotted the sweeping consequences that would follow from the discovery that living organisms might process information quantum mechanically, either at the biomolecular level, or the cellular/neuronal level [32,[52][53][54][55][56].…”
Section: Biological Information Processingmentioning
confidence: 99%
“…The components of living cells may therefore maintain an ordered structure that is compatible with retention of quantum coherence at much higher temperatures than those that would be expected to destroy the quantum state of inanimate systems [19]. Patel [53] has argued that the nucleotide bases can remain in a quantum superposition for long enough to participate in the replication process. According to quantum no-cloning theorem [58], a pure quantum state cannot be quantum mechanically replicated [18] that a quantum system can replicate into an identical one quantum fluctuation would take place.…”
Section: Biological Information Processingmentioning
confidence: 99%